Risk response towards roads is consistent across multiple species in a temperate forest ecosystem - Bastianelli, Matteo Luca; von Hoermann, Christian; Kirchner, Katrin; Signer, Johannes; Dupke, Claudia; Henrich, Maik; Wielgus, Elodie; Fiderer, Christian; Belotti, Elisa; Bufka, Luděk; Ciuti, Simone; Dormann, Carsten F.; et al. (Zenodo, 2024)
Roads can have diverse impacts on wildlife species, and while some species may adapt effectively, others may not. Studying multiple species' responses to the same infrastructure in a given area can help understand this variation and reveal the effects of disturbance on the ecology of wildlife communities. This study investigates the behavioural responses of four species with distinctive ecological and behavioural traits to roads in the protected Bohemian Forest Ecosystem in Central Europe: European roe deer ( Capreolus capreolus), a solitary herbivore; red deer ( Cervus elaphus ) a gregarious herbivore; wild boar ( Sus scrofa ), a gregarious omnivore and Eurasian lynx ( Lynx lynx ), a solitary large carnivore. We used GPS data gathered from each species to study movement behaviour and habitat selection in relation to roads using an integrated step selection analysis. For all species and sexes, we predicted increased movement rates in response to roads, selection of vegetation cover near roads and open areas after road crossings, and increased road avoidance during the day. We found remarkably similar behavioural responses towards roads across species. The behavioural adaptations to road exposure, such as increased movement rates and selection for vegetation cover, were analogous to responses to natural predation risk. Roads were more strongly avoided during daytime, when traffic volume was high. Road crossings were more frequent at twilight and at night within open areas offering food resources. Gregarious animals exposed to roads favoured stronger road avoidance over faster movements. Ungulates crossed roads more at twilight, coinciding with commuter traffic during winter. Despite differences in the ecology and behaviour of the four species, our results showed similar adaptations towards a common threat. These insights can be used by managers to promote safer road crossings where roads interfere with animals' natural behaviour. The continuous expansion of the global transportation network should be accompanied ...